Prenatally Diagnosed Cases of Binder Phenotype Complicated by Respiratory Distress in the Immediate Postnatal Period. (9th May 2016) - Blumenfeld, Yair J.; Davis, Alexis S.; Hintz, Susan R.; Milan, Kristina; Messner, Anna H.; Barth, Richard A.; Hudgins, Louanne; Chueh, Jane; Homeyer, Margaret; Bernstein, Jonathan A.; Enns, Gregory; Atwal, Paldeep; et al.
Abstract : Binder phenotype, or maxillonasal dysostosis, is a distinctive pattern of facial development characterized by a short nose with a flat nasal bridge, an acute nasolabial angle, a short columella, a convex upper lip, and class III malocclusion. We report 3 cases of prenatally diagnosed Binder phenotype associated with perinatal respiratory impairment.